Differentiate and then integrate: x^2 + 3x

To differentiate, the rule is to bring the power down to the front and multiply the expression, then take one off the value of the power, for example: d/dx(x2) = (2)x2-1 = 2x, so the answer to the the question given is: (2)x2-1 + (1)3x1-1 = 2x + 3
To integrate, you first add one to the power, and then divide the expression by the new value of the power for example: integrate(x2) = x2+1(1/3)So the answer to the question is: x2+1(1/3) + 3x1+1(1/2) = (1/3)x3 + (1/2)x2 + CRemember to add the constant of integration (C) and sometimes if we were to differentiate just a number, the expression would disappear and so we need to account for this in the integral.

Related Maths A Level answers

All answers ▸

Show that the curve y =f(x) has exactly two turning points, where f(x)= x^3 - 3x^2 - 24x - 28


Consider the function y = x.sin(x); differentiate the function with respect to x


When and how do I use the product rule for differentiation?


A curve has parametric equations x=t(t-1), y=4t/(1-t). The point S on the curve has parameter t=-1. Show that the tangent to the curve at S has equation x+3y+4=0.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences